Estimating the impacts of US LSAP's on emerging market economies' local currency bond markets - Jeffrey Moore; Sunwoo Nam; Myeongguk Suh; Alexander Tepper (Federal Reserve Bank of New York, 2013)
This paper examines whether large-scale asset purchases (LSAPs) by the Federal Reserve influenced capital flows out of the United States and into emerging market economies (EMEs) and also analyzes the degree of pass-through from long-term U.S. government bond yields to long-term EME bond yields. Using panel data from a broad array of EMEs, our empirical estimates suggest that a 10-basis-point reduction in long-term U.S. Treasury yields results in a 0.4-percentage-point increase in the foreign ownership share of emerging market debt. This, in turn, is estimated to reduce government bond yields in EMEs by approximately 1.7 basis points. Federal Reserve LSAPs, which most previous studies have found reduced ten-year U.S. Treasury yields between 60 and 110 basis points during our sample period, therefore likely contributed to U.S. outflows into EMEs and marginal reductions in longer-term EME government bond yields. These effects are qualitatively similar to conventional U.S. monetary policy easing. To assess the robustness of these estimates, we also employ event study and vector autoregression methodologies, finding broadly similar results using these methods. While these results hold in the aggregate, marginal effects vary notably across emerging market countries.
Keywords: E00; E50; G15; F30; 330; monetary policy; large-scale asset purchases; international effects; capital flows; monetary transmission